Recurrent oxidant treatment induces dysregulation in the brain transcriptome of Atlantic salmon (Salmo salar) smolts. (2022) - Carletto, Danilo; Breiland, Mette W.; Hytterød, Sigurd; Timmerhaus, Gerrit; Lazado, Carlo C.
Abstract: Peracetic acid (PAA) is an organic peroxide that produces free radicals, which contribute to its potent disinfection power. At therapeutic doses, PAA is considered a mild stressor that can trigger transient local and systemic oxidative stress in fish, but the resulting consequences in the brain have yet to be identified. Therefore, we report the brain transcriptome of Atlantic salmon ( Salmo salar ) smolts that have been periodically exposed to PAA. Fish were treated three times (every 15 days) with PAA with either short (15 min) or long (30 min) exposure periods. After the third treatment, the whole brain was collected and subjected to biochemical and transcriptomic analyses. The level of reactive oxygen species in the brain was not significantly affected by recurrent PAA treatments. Microarray analysis was performed on the whole brain and revealed 205 differentially expressed genes (DEGs), regardless of the duration of the treatment. The short exposure duration had a more considerable impact on the brain transcriptome, correlating with 70% more DEGs than the long exposure. Strikingly, the brain transcriptome was characterised by the downregulation of gene expression, especially in the short exposure group, and around 82% of the identified DEGs were downregulated. Some of the highly affected genes were key molecules of the vasotocinergic and isotocinergic systems and the corticotropin-releasing factor signalling system, indicating interference of the stress axis but could also suggest an anxiolytic effect. In addition, there were alterations in genes involved in cellular metabolism and processing, signalling and trafficking, and innate immunity, which underscores the physiological changes in the brain following recurrent PAA treatment. Overall, the transcriptomic data reveal that recurrent oxidant treatment could influence brain functions, and although the magnitude was marginal, the alterations suggested neurological adaptations of fish to PAA as a potential chemical stressor. The results identify the risks of PAA, which would be valuable in drafting a framework for its empirically driven use in fish farming. Graphical Abstract: ga1 Highlights: Reports the brain transcriptome of Atlantic salmon smolts that have been periodically exposed to peracetic acid. The level of reactive oxygen species in the brain was not significantly affected by recurrent PAA treatments. The short exposure duration had a more considerable impact on the brain transcriptome than the long exposure. Majority of the differentially expressed genes were downregulated. The vasotocinergic and isotocinergic, and corticotropin-releasing factor signalling systems were affected.